Three-dimensional analysis of miniscrew position changes during bone-borne expansion in young and late adolescent patients - Marco Migliorati; Anna De Mari; Fabio Annarumma; Hussein Aghazada; Giovanni Battista; Alessandra Campobasso; Maria Menini; Antonino Lo Giudice; Lucia H. S. Cevidanes; Sara Drago (SpringerOpen, 2023)
Abstract Introduction Maxillary expansion in patients at the end of their growth relies on the possibility to use miniscrew supported expanders to apply expansion forces directly to the midpalatal suture. Although miniscrews provide a stable anchorage unit, several studies have reported that they do not remain in exactly the same position during treatment. The aim of the present study was to analyze miniscrew position changes after the expansion using bone-borne appliances in late adolescent patients. Methods Nineteen patients (13 females, 6 males), with a mean age of 17.81 (SD = 4.66), were treated with a Bone-Borne Expander Device. The appliance was designed with 4 miniscrews: 2 in the anterior palatal area, at the third rugae level; 2 in the posterior area. A CBCT and an intraoral scan were obtained before treatment (T0), and then, a second CBCT was obtained after the expansion (T1). Data on peri-suture bone thickness were collected at T0, then the CBCTs were superimposed, and changes between mini-screws position on T0 and T1 were evaluated, both by linear and angular displacements. Results Significant longitudinal differences were found in the distance of the head and the tip of miniscrews measured at the occlusal plane, as well as angular changes. Correlations between displacement measurements and peri-suture bone thickness and height measurements were found as well. Conclusions While acting as bone anchor units, miniscrews do not remain in the same position during bone-borne expansion. The amount of displacement was related to peri-sutural total bone height and cortical thickness, especially in the anterior area of the naso-frontal maxillary complex.